(untitled) (Cultura Económica, 2018)
Mainstream business leadership practices often produce negative impacts on nature, future generations and society as a whole. Spiritual convictions may help entrepreneurial leaders to achieve their objectives in ecological, pro-social and future respecting ways. The paper presents cases of spiritually driven entrepreneurship from the USA, Europe and India and discusses the changes required for business organizations to become sustainable.